Full Concentration Gradient‐Tailored Li‐Rich Layered Oxides for High‐Energy Lithium‐Ion Batteries. Issue 2 (30th November 2020) - Wu, Tianhao; Liu, Xiang; Zhang, Xu; Lu, Yue; Wang, Boya; Deng, Qingsong; Yang, Yubo; Wang, Errui; Lyu, Zhongtian; Li, Yaoqian; Wang, Yongtao; Lyu, Yan; et al.
Abstract: Lithium‐rich layered oxides (LLOs) are prospective cathode materials for next‐generation lithium‐ion batteries (LIBs), but severe voltage decay and energy attenuation with cycling still hinder their practical applications. Herein, a series of full concentration gradient‐tailored agglomerated‐sphere LLOs are designed with linearly decreasing Mn and linearly increasing Ni and Co from the particle center to the surface. The gradient‐tailored LLOs exhibit noticeably reduced voltage decay, enhanced rate performance, improved cycle stability, and thermal stability. Without any material modifications or electrolyte optimizations, the gradient‐tailored LLO with medium‐slope shows the best electrochemical performance, with a very low average voltage decay of 0.8 mV per cycle as well as a capacity retention of 88.4% within 200 cycles at 200 mA g −1 . These excellent findings are due to spinel structure suppression, electrochemical stress optimization, and Jahn‐Teller effect inhibition. Further investigation shows that the gradient‐tailored LLO reduces the thermal release percentage by as much as about 41% when the battery is charged to 4.4 V. This study provides an effective method to suppress the voltage decay of LLOs for further practical utilization in LIBs and also puts forward a bulk‐structure design strategy to prepare better electrode materials for different rechargeable batteries. Abstract : A precise elemental gradient design for practical lithium‐rich layered oxide (LLO) agglomerated spheres is developed, providing a unique tool for the optimization of voltage retention and electrochemical/thermal stability of lithium‐ion batteries. The effects of elemental gradient on the LLOs, especially from a mechanical/electrochemical stress point of view, are quantitively elucidated for stability evaluation.